2023
DOI: 10.56093/ijas.v93i5.103296
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring productivity advantages through Cluster Frontline Demonstrations (CFLD)-pulses: Nationwide experiences

Abstract: The present study is the analysis of large scale data (31949 ha area and 79873 farmers) generated through the CFLD on pulses across the major pulses growing states under the ICAR-ATARIs of Kanpur (Uttar Pradesh), Jodhpur (Rajasthan), Pune (Maharashtra), Patna (Bihar), Jabalpur (Madhya Pradesh), Kolkata (West Bengal), Guwahati (Assam), Shillong (Meghalaya), Hyderabad (Andhra Pradesh), Bengaluru (Karnataka) and Patna (Bihar). The pulse crops included in this analysis were from all three growing seasons: kharif (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…This may due to unawareness about high yielding varieties, increased extension yield gap as a result of farmers' ignorance to adopt better farming practices; this suggests that farmers need to be strongly encouraged to embrace improved farming practices in pulse crop rather than sticking with traditional local methods. These findings in line with findings reported by Kumar et al (2022) [5] , Singh et al (2020) [11] , Dubey et al (2022) [2] and Sunitha et al (2020c) [15] reported that the highest extension gap was observed in pigeon pea. This extension yield gap may minimized by promoting some extension activities, organizing awareness training programme to the farmers about high yielding varieties and organizing Krishimela's.…”
Section: Extension Gapsupporting
confidence: 90%
See 1 more Smart Citation
“…This may due to unawareness about high yielding varieties, increased extension yield gap as a result of farmers' ignorance to adopt better farming practices; this suggests that farmers need to be strongly encouraged to embrace improved farming practices in pulse crop rather than sticking with traditional local methods. These findings in line with findings reported by Kumar et al (2022) [5] , Singh et al (2020) [11] , Dubey et al (2022) [2] and Sunitha et al (2020c) [15] reported that the highest extension gap was observed in pigeon pea. This extension yield gap may minimized by promoting some extension activities, organizing awareness training programme to the farmers about high yielding varieties and organizing Krishimela's.…”
Section: Extension Gapsupporting
confidence: 90%
“…Results depicts that the demonstrated varieties performed better results. Similar results quoted by Singh et al (2020) [11] , Kumar et al (2010) [6] and Sunitha et al (2020b) [14] that higher technology index may be due to incidence of pest and disease, soil fertility condition and climatic conditions. One probable explanation for low yields and a higher technology index in both crops is poor field establishment during the early vegetative stage caused by water stress under rainfed farming with irregular rainfall distribution, a protracted dry spell, and growing pressure from diseases and insect pests.…”
Section: Technology Indexsupporting
confidence: 83%
“…Improved methods also outperformed farmers' practices in terms of incremental BCR (30.1), gross water productivity (16.58m -3 ), net water productivity (11.89m -3 ), SYI (0.63), SVI (0.47) and water expense efficiency (74.92 kg ha -1 cm -1 ). Rabi pulses had lower SYI (0.45-0.60) as compared to Kharif (0.67-0.83) with black gram SYI 0.67 and summer (0.67) indicating clearly that Rabi pulses can be further exploited for their potential yield especially in lentil and chickpea by improving per unit production to get highest SYI level (Singh et al, 2023).…”
Section: Sustainability Yield Index and Sustainability Value Indexmentioning
confidence: 96%